Clarifying the brand personality construct in Malaysia - Mohtar, Mozard; Rudd, John M.; Evanschitzky, Heiner (Emerald, 2019)
Purpose: This paper aims to investigate the variations in brand personality trait items to describe both global and local brands in Malaysia. Design/methodology/approach: The authors adopted both factor analytic and experimental methods to investigate the internal and external validity of Malaysia brand personality (MBP) scale. They followed a stringent scale development process that ensures the scale conform to psychometric properties. Findings: In seven studies, the results show that the 22-item four-factor Malaysian brand personality scale adheres to strong psychometric properties of scale development process. The findings further indicate that there are seven indigenous traits, while most traits emerge from factor analyses originate from studies of Aaker (1997) and colleagues (2001). This confirms universality of some brand personality traits and dimensions. Research limitations/implications: Within the limits of the study, we did not examine the MBP facet level, and were confined to those respondents in Klang Valley only. Practical implications: The MBP scale enables marketing managers in Malaysia to focus on brand personality dimensions that their customers can relate to. In other words, marketing communications can be more efficient when managers can identify brand personality traits that enhance customers’ behaviors and profitability. Originality/value: Malaysia is a multicultural and multiethnic country which is increasingly becoming the focus of international brand expansion. The authors view that the development of the MBP scale is timely and should provide managers further insights into the brand personality structure that is relevant in Malaysia. © 2019, Emerald Publishing Limited.